A genetically encoded biosensor reveals spatiotemporal variation in cellular phosphate content in Brachypodium distachyon mycorrhizal roots. Issue 5 (5th April 2022) - Zhang, Shiqi; Daniels, Dierdra A.; Ivanov, Sergey; Jurgensen, Lucas; Müller, Lena M.; Versaw, Wayne K.; Harrison, Maria J.
Summary: Arbuscular mycorrhizal (AM) symbiosis is accompanied by alterations to root cell metabolism and physiology, and to the pathways of orthophosphate (Pi) entry into the root, which increase with Pi delivery to cortical cells via arbuscules. How AM symbiosis influences the Pi content and Pi response dynamics of cells in the root cortex and epidermis is unknown. Using fluorescence resonance energy transfer (FRET)‐based Pi biosensors, we mapped the relative cytosolic and plastidic Pi content of Brachypodium distachyon mycorrhizal root cells, analyzed responses to extracellular Pi and traced extraradical hyphae‐mediated Pi transfer to colonized cells. Colonized cortical cells had a higher cytosolic Pi content relative to noncolonized cortical and epidermal cells, while plastidic Pi content was highest in cells at the infection front. Pi application to the entire mycorrhizal root resulted in transient changes in cytosolic Pi that differed in direction and magnitude depending on cell type and arbuscule status; cells with mature arbuscules showed a substantial transient increase in cytosolic Pi while those with collapsed arbuscules showed a decrease. Directed Pi application to extraradical hyphae resulted in measurable changes in cytosolic Pi of colonized cells 18 h after application. Our experiments reveal that cells within a mycorrhizal root vary in Pi content and Pi response dynamics.